Bacterial DNA activates human neutrophils by a CpG‐independent pathway - Trevani, Analía Silvina (2003)
Bacterial DNA stimulates macrophages, monocytes, B lymphocytes, NK cells, and dendritic cells in a CpG‐dependent manner. In this work we demonstrate that bacterial DNA, but not mammalian DNA, induces human neutrophil activation as assessed by L‐selectin shedding, CD11b upregulation, and stimulation of cellular shape change, IL‐8 secretion, and cell migration. Induction of these responsesis not dependent on the presence of unmethylated CpG motifs, as neutrophil stimulatory properties were neither modified by CpG‐methylation of bacterial DNA nor reproduced by oligonucleotides bearing CpG motifs. We found that human neutrophils express Toll‐like receptor (TLR) 9 mRNA. However, as expected for a CpG‐independent mechanism, activation does not involve a TLR9‐dependent signaling pathway; neutrophil stimulation was not prevented by immobilization of bacterial DNA or by wortmannin or chloroquine, two agents that inhibit TLR9 signaling. Of note, both single‐stranded and double‐stranded DNA were able to induce activation, suggesting that neutrophils might be activated by bacterial DNA at inflammatory foci even in the absence of conditions required to induce DNA denaturation. Our findings provide the first evidence that neutrophils might be alerted to the presence of invading bacteria through recognition of its DNA via a novel mechanism not involving CpG motifs.